A comprehensive modelling and experimental approach to study the diffusion-controlled dissolution in pitting corrosion. (1st July 2021) - Nguyen, Van Anh; Newman, Roger C.
Highlights: A full mass transport model is coupled with artificial pit experiments. In dilute NaCl solutions, the limiting current density increases due to migration. The presence of Na + at the pit bottom is significant in high bulk NaCl solutions. Na + at the pit bottom increases the limiting current density to some degree. The diffusivity and the solubility of dissolving metal ions were obtained. Abstract: The novelty of this paper is that we consider the "diffusion-controlled" dissolution of a metal in a pit from a more advanced point of view, such that the limiting anodic current density ( iL ) varies with the bulk NaCl concentration in accordance with a mathematical model that includes ion migration. The full mass transport model was coupled with artificial pit experiments to obtain critical parameters for pit stability. At above 2.5 M NaCl, the conventional diffusion-only model gives reasonably accurate results, but the effect of Na + at the bottom of the pit on iL and the metal's solubility should be considered.